Community composition and diversity of phytoplankton in relation to environmental variables and seasonability in a tropical mangrove estuary - Saifullah, A. S. M.; Mustafa Kamal, Abu Hena; Idris, Mohd Hanafi; Rajaee, Amy Halimah (Elsevier, 2019)
This paper presents the aspects of phytoplankton communities along a tropical mangrove estuary inSarawak, Malaysia. Data were collected monthly from the study area from January 2013 to December2013 and was pooled into seasons to examine the influence of seasonality. The estuary revealedrelatively species-rich, and a total of 102 species under 43 genera were recorded comprising 6 speciesof Cyanophyceae; 4 species of Chlorophyceae; 62 species of Bacillariophyceae and 30 species ofDinophyceae. The species composition, as well as the mean abundance (cellsL-1) of phytoplankton,were found in order of Bacillariophyceae>Dinophyceae> Cyanophyceae> Chlorophyceae. Mean abun-dance of phytoplankton ranged from 5694 to 88890 cellsL−1over the study period with its highervalue in the dry season. Species recorded from the estuary were dominated byPleurosigma normanii,Coscinodiscussp,Coscinodiscus centralis,Coscinodiscus granii,Dinophysis caudata,Ceratium carriense,Ceratium fusus, andCeratium lineatum. Abundance of phytoplankton demonstrated positive correlationwith chlorophylla(r=0.69), ammonium (r=0.64) and silica (r=0.64). Significant differences (ANOSIMand nMDS) were observed in the species community structure between intermediate and the wetseason. Canonical correspondence analysis (CCA) showed that most of the species assemblages werepositively correlated with surface water temperature, salinity, pH, ammonium and nitrate in theintermediate and dry season towards larger species composition in the respective seasons whereassilica showed influence on the species assemblage in the wet season. The findings suggest that theSibuti mangrove estuary is productive in terms of diversified phytoplanktons and their variability inassemblage, those are influenced by the hydrological and biological factors.